تأثير طريقة ألعاب اللغوية على التحصيل الدراسى اللغة العربية - Nurul Fauziyah; Zakiyatul Abidah; Muhammad Husain (Kilmatuna: Journal Of Arabic Education, 2021)
The process of teaching Arabic in Junior high school 16 Nurul Hidayah Banyubang Solokoro Lamongan is less effective, students face different problems, especially in the lack of educational attainment of Arabic because students are not interested in learning Arabic. Therefore, the relevant teaching method, which is able to improve educational attainment, needs Arabic, one of which is the method of language games (guess the word) on the educational achievement of Arabic for students in the eighth grade (a) of the Junior high school 16 Nurul Hidayah Banyubang Solokoro Lamongan.This research uses the experimental method with tribal testing and the one group pretest-posttest. The community in this research students in Junior high school 16 Nurul Hidayah. The sample made the students 8th grade (a) and a total of 28 students. Even the researcher takes that sample with the aim of promoting educational collection. How to get data with the test, interview, note, resolution and documentation.By the results of that computer the result is 33.21 and d.b is N-1 = 28-1 =27 and the T-tes panel (utilities 1) which uses one set indicating the role of large numbers 0.05 is 1,703 and 0.01 is 2,473. With regard to the H_0 acceptance or rejection may be H_a accepted if the result t_tabel < t_test the level of importance (signifikasi) 0.05 and 0.01.